Carbon Emission Analysis of Construction Industry in Sichuan Province Driven by “Double Carbon” Targets - Zhou Wei; Gan Yuanjing; Wei Leili; Li Jialing; Huang Rong (E3S Web of Conferences)
The “dual carbon” goal is a two-stage carbon reduction goal proposed by China, including carbon peaking and carbon neutrality, which reflects China’s firm determination to combat climate change and realize green development. Carbon emissions from the construction industry are one of the main sources of carbon emissions growth in China, so analyzing carbon emissions from the construction industry can help to achieve China’s “double carbon” goal. In this paper, Sichuan Province is chosen to analyze its total carbon emissions from the construction industry from 2012 to 2022.Carbon Emission Factor Approach (CEFA) is mainly adopted to calculate the total carbon emissions of Sichuan Province, explore the carbon emissions of the entire industrial chain of the construction industry in Sichuan Province. The data of the carbon emission calculation results of the construction industry in Sichuan Province are preliminarily analyzed. Based on the analysis, three policy suggestions are put forward to promote the deep emission reduction of the construction industry in Sichuan Province, which lays a foundation tapping the potential of carbon emission reduction in the construction industry in Sichuan Province, which lays the foundation for exploring the potential of carbon emission reduction in the construction industry in Sichuan Province.